Antiparasitic hybrids of Cinchona alkaloids and bile acids - Leverrier, Aurélie (2013)
A series of 16 hybrids of Cinchona alkaloids and bile acids (4a–h, 5a–h) was prepared by means of a Barton–Zard decarboxylation reaction. Quinine, quinidine, cinchonine and cinchonidine were functionalized at position C-2 of the quinoline nucleus by radical attack of a norcholane substituent. The newly synthesized hybrids were evaluated in vitro for their antitrypanosomal, antileishmanial and antiplasmodial activities, along with their cytotoxicity against WI38, a normal human fibroblast cell line. Seven compounds (4d, 4f, 4h, 5b, 5d, 5f, 5h) showed promising trypanocidal activity with IC50 values in the same range as the commercial drug suramine. Moreover all the 16 hybrids showed antiplasmodial activity (IC50 ≤ 6 μg/ml), particularly those containing a nor-chenodeoxycholane moiety (4b, 4d, 4f, 4h, 5b, 5d, 5f, 5h) with IC50 values comparable to those of the natural alkaloids, and selectivity indices in the range of 5.6–15.7.